INTERNALISASI KEBIJAKAN PEMERINTAH ACEH BERDASARKAN UNDANG –UNDANG NOMOR 11 TAHUN 2006 TENTANG PEMERINTAH ACEH - Nellis Mardhiah; Rahma Hidayati; Mursyidin Mursyidin (Universitas Teuku Umar, 2018)
law number 11 Year 2006 was the implementation of the contents of the notes kesefahaman a memorandum of understanding (MoU) to Helsinki Government Indonesia with the free Aceh Movement (GAM) on 15 August 2005. This MOU is the beginning of a permanent peace in Aceh. Objective of writing this was the development of the implementation of the BAL after peace in Aceh. This research with qualitative and descriptive analysis method, by using the technique of observes and interviews. The goal of his research can contribute to the legislature in order to understand the stages of the process of legislation happen polemic in the realization of this legislation as BAL due to rules of normative binding, but in terms of the realization of the implementation of the special autonomy policy is not as easy as normative rules contained in regulation perundangan-undangan. It is given the legal system in Aceh. The policy objectives have not yet reached target BAL of the Aceh government readiness in meeting the needs of the community. In addition, the implementation of this legislation requires specific strategies and the DPRA capacity is crucial in separating political and administrative functions for the achievement of the input, output and outcomes in public life in post peace in Aceh.Keywords: Development Of The BAL. DPRA. Aceh Peace